(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The present study included test the effectiveness of Turbinoid and Alkaloid compounds extracts from pure leaves of Devil’s Claw Ibicella lutea on life performance of false armyworm insect Lucania loreyi, the Turbinoid compounds extract had a clear effect on the various insect lifestyle, the percentage of eggs destruction in the Turbinoid and Alkaloid compounds extract at a concentration of 2.0 mg/ ml reached (50.0 and 46.7%), respectively, compared with the control treatment that reach (0.0%), The percentage of the destruction of first and sixth larval instar was (90.3 and 73.3%) when transacted with Turbinoid compounds extract respectively at the concentration of 2.0 mg/ ml, while the percentage of destruction of first and sixth larval instar that transacted with Alkaloid compounds extract was reach (90 and 56.7 %) respectively at the concentration of 2.0 mg/ ml, the highest percentage for pupa destruction was reached about 80% when transacted with Turbinoid compounds extract at concentration of 2.0 mg/ ml compared with Alkaloid compounds extract which reached 43.3% at concentration of 2.0 mg/ ml, and the percentage of adult destruction reached 63.3% when transacted with Turbinoid compounds extract at a concentration of 2.0 mg/ ml and reached 40.0% with alkaloid extract, The accumulative percentage of immature phases destruction, when transacted with Turbinoid and Alkaloid compounds, extract reached about (100 and 83.3%), respectively, at a concentration of 2.0 mg/ ml.